Biocomputing 2018 2017
DOI: 10.1142/9789813235533_0011
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of disease pathways in the human interactome

Abstract: Discovering disease pathways, which can be defined as sets of proteins associated with a given disease, is an important problem that has the potential to provide clinically actionable insights for disease diagnosis, prognosis, and treatment. Computational methods aid the discovery by relying on protein-protein interaction (PPI) networks. They start with a few known disease-associated proteins and aim to find the rest of the pathway by exploring the PPI network around the known disease proteins. However, the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 34 publications
(78 reference statements)
3
72
0
Order By: Relevance
“…In agreement with previous studies ( Agrawal et al 2018 ; Menche et al 2015 ), we found that proteins associated with a single disease (see Fig. 1 a ) form several connected components in the hPIN, instead of a unique connected entity (see Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies ( Agrawal et al 2018 ; Menche et al 2015 ), we found that proteins associated with a single disease (see Fig. 1 a ) form several connected components in the hPIN, instead of a unique connected entity (see Fig.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, defective or dysregulated proteins can disrupt PPIs, clog important signalling pathways and cause disease phenotypes ( Taylor and Wrana 2012 ). In fact, it has been reported that the proteins associated with a single disease agglomerate non-randomly in the same region of the hPIN, forming one or several connected components known as the disease module (DM) ( Agrawal et al 2018 ; Menche et al 2015 ). Consequently, disease-related proteins are more likely to have PPIs with each other than with random proteins.…”
Section: Introductionmentioning
confidence: 99%
“…interactions [30], [31]. • P-P-Pathways is a biological network of physical interactions between proteins in humans [32].…”
Section: A Synthetic Experimentsmentioning
confidence: 99%
“…Network science studies entities (as nodes) and their pairwise relationships (as edges) and can be a powerful tool to discover interaction patterns among biological components. Previous network‐based studies have demonstrated that cellular interaction networks, including protein–protein interaction networks, gene coexpression networks, and metabolic networks, can be used to understand the molecular basis of disease‐gene associations (Agrawal, Zitnik, & Leskovec, 2018; Almasi & Hu, 2019; Barabasi & Oltvai, 2004; Hu et al, 2018; Milenković & Pržulj, 2008; Palla, Derényi, Farkas, & Vicsek, 2005).…”
Section: Introductionmentioning
confidence: 99%